Good-quality diet in the early years may have a positive effect on academic achievement - Nyaradi, A.; Li, Jianghong; Foster, Jonathan; Hickling, S.; Jacques, Angela; O'Sullivan, T.; Oddy, W. (Wiley-Blackwell Publishing Ltd., 2016)
Aim: The aim of this study was to investigate the associations between early diet and academic performance during childhood. Methods: Participants were from the Western Australian Pregnancy Cohort (Raine) Study (n = 2287). Frequency of consumption of food and beverages was collected at the one-, two- and three-year follow-ups, using a 24-hour food recall. Diet scores were developed from the number of eating occasions. The Western Australian Literacy and Numeracy Assessment (WALNA) data from grades five (age 10) and seven (age 12) were linked to the Raine study using The Western Australian Data Linkage System. The association between diet scores and WALNA scores was assessed using multivariate linear regression models. Results: A higher (i.e. better quality) diet score at one year of age was associated with significantly higher scores in mathematics, reading, writing and spelling at both grades five and seven. Associations were observed between a higher diet score at two years and academic scores for mathematics, writing and spelling at grade seven. Higher dairy consumption at ages one, two and three, and higher fruit consumption at age one were associated with higher academic scores at all ages. Conclusion: Quality of early diet may be a predictor for later academic achievement.